2019
DOI: 10.3390/nu11040853
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Quality of Australian Supermarkets’ Policies That Can Impact Public Health Nutrition, and Evidence of Their Practical Application: A Cross-Sectional Study

Abstract: Improving population diets is a public health priority, and calls have been made for corporations such as supermarkets to contribute. Supermarkets hold a powerful position within the food system, and one source of power is supermarket own brand foods (SOBFs). Many of the world’s largest supermarkets have corporate social responsibility (CSR) policies that can impact public health, but little is known about their quality or practical application. This study examines the nature and quality of Australian supermar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Some parents stated that they experienced food insecurity, which further exacerbated unhealthy feeding practices. American research with parents of two-year-olds from food-insecure households reported more pressure to eat energy-dense nutrient-poor foods [ 57 ] and food insecurity has been found to be a factor in parents encouraging their children (aged six months to five years) to eat everything on their plate due to the uncertainty of food availability. Although, parents from food-insecure households were motivated to provide healthy meals, and had goals to enhance positive family relationships through family meals; barriers, such as time and food costs, influenced these goals, resulting in parents adopting less healthy feeding practices [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some parents stated that they experienced food insecurity, which further exacerbated unhealthy feeding practices. American research with parents of two-year-olds from food-insecure households reported more pressure to eat energy-dense nutrient-poor foods [ 57 ] and food insecurity has been found to be a factor in parents encouraging their children (aged six months to five years) to eat everything on their plate due to the uncertainty of food availability. Although, parents from food-insecure households were motivated to provide healthy meals, and had goals to enhance positive family relationships through family meals; barriers, such as time and food costs, influenced these goals, resulting in parents adopting less healthy feeding practices [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although, parents from food-insecure households were motivated to provide healthy meals, and had goals to enhance positive family relationships through family meals; barriers, such as time and food costs, influenced these goals, resulting in parents adopting less healthy feeding practices [ 58 ]. Parents, particularly those that are food insecure, need assistance to balance dietary goals, and food literacy knowledge, skills, and resources to achieve healthy eating practices [ 38 , 57 ]. Linking parents to food relief services may provide additional support for such families.…”
Section: Discussionmentioning
confidence: 99%
“…The scoping review was conducted following the protocol explained by Arksey and O'Malley, the PRISMA extension for Scoping Reviews and others [36][37][38][39][40]. The protocol (available on request from the corresponding author) includes five steps: (1) define the research question; (2) identify relevant studies through a search strategy; (3) select studies following certain criteria; (4) data charting (extract, synthesize and interpret data); and (5) summarize and report the results.…”
Section: Methodsmentioning
confidence: 99%
“…Supermarkets are an important source of ingredients, but they also sell ultra-processed foods, and in some places this is their predominant offer 25. Supermarkets could be encouraged to move away from ultra-processed foods—for example, by mandatory requirements to report sales of ultra-processed foods as a proportion of all sales 46…”
Section: Strategies To Increase Consumption Of Hand Prepared Foodmentioning
confidence: 99%